Etika Komunikasi Islam pada Aktor Politik Indonesia: Kajian Wacana di Media Online - Masran (Dakwah Institut PTIQ Jakarta, 2022)
This study aims to explore and analyze the ethical problems of communication between Indonesian political actors on social media (via news on detik.com.kompas.com, CNN.com) which indicate